Heterogeneous consumers, segmented asset markets, and the real effects of monetary policy - Enders, Zeno (CESifo working papers, 2017)
This paper proposes a novel mechanism by which changes in the distribution of money holdings have real effects. Specifically, I develop a flexible-price model of segmented asset markets that generates real aggregate effects of monetary policy through the dependence of optimal markups on the heterogeneity of money holdings. Because varieties of consumption bundles are purchased sequentially, newly injected money disseminates slowly throughout the economy via second-round effects. The model predicts a short-term inflation-output trade-off, a liquidity effect, countercyclical markups, and procyclical wages after monetary shocks. Among other correlations of financial variables, it also reproduces the empirical, negative relationship between changes in the money supply and markups.